2009
DOI: 10.1539/joh.o9006
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure Levels of Bisphenol A among Chinese Workers

Abstract: The purpose of this study was to assess ambient Bisphenol A (BPA) levels in workplaces and urine BPA levels of workers. Methods: Workers in epoxy resin and BPA manufacturing factories were recruited. Personal samples for airborne BPA were taken in the workshops and spot urine samples were collected from workers before and after their shifts. The samples were assayed with highperformance liquid chromatography with a fluorescence detector. TWA 8 of airborne PBA in the workplaces and biological BPA burden of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 15 publications
9
33
0
1
Order By: Relevance
“…We therefore measured the internal concentration of free BPA by liquid chromatography-tandem mass spectrometry analysis (Axys Analytical Services). We found that an external dose of 1 mM BPA corresponds to an uptake level of 2 μg/g (2 ppm) of worm extract, a value within the range of internal concentrations of BPA detected in several rodent exposure models (21)(22)(23) and of serum levels in occupational exposure cases (24). It is also an order of magnitude higher than the levels of BPA found in human placental tissues (23,25).…”
Section: Bpa Exposure Results In Decreased Broodsupporting
confidence: 54%
See 1 more Smart Citation
“…We therefore measured the internal concentration of free BPA by liquid chromatography-tandem mass spectrometry analysis (Axys Analytical Services). We found that an external dose of 1 mM BPA corresponds to an uptake level of 2 μg/g (2 ppm) of worm extract, a value within the range of internal concentrations of BPA detected in several rodent exposure models (21)(22)(23) and of serum levels in occupational exposure cases (24). It is also an order of magnitude higher than the levels of BPA found in human placental tissues (23,25).…”
Section: Bpa Exposure Results In Decreased Broodsupporting
confidence: 54%
“…However, it is likely that both our results and those of Susiarjo and colleagues (9) represent the reproductive outcome following elevated BPA exposure. Therefore, our studies bear relevance to occupational exposure studies in humans (24,45), and particularly to fetal and neonate exposure levels, as suggested by the up to 10 times higher levels of BPA detected in premature infants in neonatal intensive care units (46).…”
Section: Discussionmentioning
confidence: 70%
“…The results based on these urine BPA samples have been previously reported (He et al, 2009a(He et al, , 2009b. Although the current urine BPA level was not used as a measure of exposure level for the index pregnancy, it was used as an additional measure to verify the validity of classification of BPA exposure (see later).…”
Section: Measurement Of Bpa Exposurementioning
confidence: 81%
“…Although most intake occurs from ingestion, people who are engaged in the manufacturing or use of BPA (or related chemicals) can easily absorb it through the skin, or take it up via inhalation (He et al 2009b ;Kaddar et al 2009 ;Geens et al 2012 ).…”
Section: Sources and Routes Of Bisphenol A Exposurementioning
confidence: 99%